RATE-CONSTANT FOR REACTION OF CH (X2-PI) WITH KETENE - Hancock, G; Heal, M (1992)
A bimolecular rate constant for the reactive removal of CH (X 2Π) by ketene (CH2CO) has been measured under pseudo-first-order conditions using multiphoton dissociation of CH2CO at 308 nm to generate the radicals and laser induced fluorescence to detect them. A value of (2.4 ± 0.2) × 10-10 cm3 molecule-1 s-1 was obtained at room temperature (295 ± 2 K).